2006
DOI: 10.1002/cne.21152
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of MT1 melatonin receptor immunoreactivity in the human hypothalamus and pituitary gland: Colocalization of MT1 with vasopressin, oxytocin, and corticotropin‐releasing hormone

Abstract: Melatonin is implicated in numerous physiological processes, including circadian rhythms, stress, and reproduction, many of which are mediated by the hypothalamus and pituitary. The physiological actions of melatonin are mainly mediated by melatonin receptors. We here describe the distribution of the melatonin receptor MT1 in the human hypothalamus and pituitary by immunocytochemistry. MT1 immunoreactivity showed a widespread pattern in the hypothalamus. In addition to the area of the suprachiasmatic nucleus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(103 citation statements)
references
References 84 publications
(93 reference statements)
5
95
1
2
Order By: Relevance
“…The possible mechanism by which melatonin can modify the vasopressinergic and oxytocinergic neurones activity includes specific G protein-coupled membrane receptors, called MT 1 and MT 2 , activation of which inhibits the synthesis of cAMP [21,24]. These receptors are situated mainly in the pars tuberalis of the pituitary [25] and in the hypothalamic suprachiasmatic (SCN) [15,[26][27][28] as well as magnocellular SON and PVN nuclei [29]. It has been found that AVP-containing cells in the SCN express both MT 1 [27] and MT 2 [28] melatonin receptors and melatonin inhibits AVP release from cultured SCN neurones [15,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible mechanism by which melatonin can modify the vasopressinergic and oxytocinergic neurones activity includes specific G protein-coupled membrane receptors, called MT 1 and MT 2 , activation of which inhibits the synthesis of cAMP [21,24]. These receptors are situated mainly in the pars tuberalis of the pituitary [25] and in the hypothalamic suprachiasmatic (SCN) [15,[26][27][28] as well as magnocellular SON and PVN nuclei [29]. It has been found that AVP-containing cells in the SCN express both MT 1 [27] and MT 2 [28] melatonin receptors and melatonin inhibits AVP release from cultured SCN neurones [15,28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the interaction of melatonin with its receptors present in other brain regions cannot be excluded. Namely, a small amount of MT 1 receptors has been observed in human posterior pituitary [29], which may suggest that melatonin exerts its influence on the AVP/OT release acting not only at the level of the hypothalamus, but also directly on the axonal endings located in the neurohypophysis. The anatomical basis for such a hypothesis is not only the existence of direct neuronal projection from the SCN to PVN and SON, but also the fact that the explant we used for the present in vitro experiments contained the whole hypothalamo-neurohypophysial system.…”
Section: Discussionmentioning
confidence: 99%
“…If pregnancy occurs, the number of differentiated decidual cells and the synthesis of decidual PRL increase after implantation, reaching a peak between 20 and 25 weeks, and stopping close to term. 17 Jabbour and Critchley 37 confirmed the expression of the PRL receptor (PRL-R) in the endometrium and decidua. Immunohistochemical and in situ hybridization methods have revealed that PRL-R is expressed strongly by the glandular epithelium and the stromal cells of the decidualized endometrium.…”
Section: Melatonin and Reproductionmentioning
confidence: 94%
“…15 Experimental studies with female rats and hamsters reported that removal of the pineal gland leads to a decrease in melatonin levels with consequent premature vaginal opening, ovarian hypertrophy, increased cornification of vaginal cells and chronic anovulation, effect that can be reversed after administration of melatonin. 16,17 In contrast, according to Murcia-García et al, treatment with melatonin reduces the weight of ovaries and delays sexual maturation in rats. 18 Melatonin replacement is capable of reversing continuous and transitional anovulatory estrous cycle in rats caused by exposure to continuous light or due to the removal of the pineal.…”
Section: Melatonin and Reproductionmentioning
confidence: 98%
“…A colocalization of melatonin receptors and ADH neurons in the suprachiasmatic, paraventricular and supraoptic nuclei has been described, suggesting that melatonin might directly modulate the hypothalamic-pituitary-adrenal axis and thus might also have an impact on the antidiuretic effect of ADH [60]. Besides, a reninangiotensin system in the brain seems to modulate melatonin synthesis.…”
Section: Other Hormonesmentioning
confidence: 99%